Gabra5 plays a sexually dimorphic role in POMC neuron activity and glucose balance - Pei, Zhou; He, Yang; Bean, Jonathan C.; Yang, Yongjie; Liu, Hailan; Yu, Meng; Yu, Kaifan; Hyseni, Ilirjana; Cai, Xing; Liu, Hesong; Qu, Na; Tu, Longlong; et al. (Frontiers in Endocrinology, 2022)
Pro-opiomelanocortin (POMC) neurons are important for the regulation of body weight and glucose balance. The inhibitory tone to POMC neurons is mediated primarily by the GABA receptors. However, the detailed mechanisms and functions of GABA receptors are not well understood. The α5 subunit of GABAA receptor, Gabra5, is reported to regulate feeding, and we found that Gabra5 is highly expressed in POMC neurons. To explore the function of Gabra5 in POMC neurons, we knocked down Gabra5 specifically from mature hypothalamic POMC neurons using the clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9 strategy. This POMC-specific knock-down of Gabra5 did not affect body weight or food intake in either male or female mice. Interestingly, the loss of Gabra5 caused significant increases in the firing frequency and resting membrane potential, and a decrease in the amplitude of the miniature inhibitory postsynaptic current (mIPSC) in male POMC neurons. However, the loss of Gabra5 only modestly decreased the frequency of mIPSC in female POMC neurons. Consistently, POMC-specific knock-down of Gabra5 significantly improved glucose tolerance in male mice but not in female mice. These results revealed a sexually dimorphic role of Gabra5 in POMC neuron activity and glucose balance, independent of body weight control.